Down‐regulation of microRNA‐34c‐5p alleviates neuropathic pain via the SIRT1/STAT3 signaling pathway in rat models of chronic constriction injury of sciatic nerve. Issue 3 (24th March 2020) - Mo, Yanshuai; Liu, Benjuan; Qiu, Shuang; Wang, Xueqin; Zhong, Lina; Han, Xiao; Mi, Fuli
Abstract: Neuropathic pain is an unfavorable pathological pain, often persistent over time, thus leading to significant impairment of quality of life and public health burden. Notably, microRNAs have been implicated in the pathophysiological process of neuropathic pain. The potential mechanism by which miR‐34c‐5p functions in neuropathic pain remains unclear. This study aimed to test the hypothesis that miR‐34c‐5p can modulate neuropathic pain in rat models with chronic constriction injury (CCI) of sciatic nerve, via interaction with the SIRT1/STAT3 signaling pathway SIRT1 was validated as a target gene of miR‐34c‐5p and could be negatively regulated by miR‐34c‐5p. We induced miR‐34c‐5p overexpression/inhibition, SIRT1 knockdown, and STAT3 knockdown in the model rats to assess pain behavior patterns. Meanwhile, dorsal root ganglion (DRG) was transduced with overexpression or knockdown of miR‐34c‐5p or lipopolysaccharide to induce the production of inflammatory factors. It was observed that miR‐34c‐5p was up‐regulated, and SIRT1 was under‐expressed in the DRG neurons of dorsal spinal cords of the CCI rats. Furthermore, the ectopic expression of miR‐34c‐5p and knockdown of SIRT1 in CCI rats resulted in increased hyperalgesia and inflammation, corresponding to reduced paw withdrawal threshold and paw withdrawal latency, and elevated levels of IL‐6, IL‐1β, and TNF‐α. More importantly, miR‐34c‐5p inhibition reduced the hyperalgesia and inflammation by blocking the STAT3 signaling pathway through up‐regulation of SIRT1. Conjointly, our results indicated that the down‐regulation of miR‐34c‐5p could potentially provide sustained relief in neuropathic pain by promoting SIRT1 expression through STAT3 signaling pathway inactivation. Abstract : This study aims to clarify the effects of miR‐34c‐5p‐mediated SIRT1/STAT3 signaling pathway on neuropathic pain in rat models with chronic constriction injury (CCI) of sciatic nerve. MicroRNA‐34c‐5p (miR‐34c‐5p) targets and down‐regulates the expression of sirtuin‐1 (SIRT1), consequently promoting the activation of signal transducer and activator of transcription 3 (STAT3) signaling pathway and increasing the expression of interleukin‐6 (IL‐6), interleukin‐1 beta (IL‐1β), and tumor necrosis factor‐α (TNF‐α), which ultimately leads to neuropathic pain. These findings may serve as novel clues for the molecular mechanism behind neuropathic pain. These results establish the miR‐34c‐5p/SIRT1/STAT3 axis as a potential physiologically validated target for neuropathic pain management.